PHARMACODYNAMICS OF FOENICULUM VULGARE AGAINST ULCER, INFLAMMATION, HEPATOTOXICITY AND NEPHROTOXICITY - M. Tanveer1; A. Shehzad; 2; M. S. Butt; M. Shahid (Journal of Animal and Plant Sciences, 2020)
The proposed study was designed to assess the phytotherapic potential of locally cultivated fennel seeds against certain lifestyle associated disarrays. Fennel seed powder was subjected to conventional solvent extraction (CSE) and supercritical fluid extraction (SFE), followed by evaluation of health improving perspectives of fennel extracted phytoconstituents. The in vivo phase comprised of five studies with three groups in each based upon the diets i.e. control (D0), nutraceuticalCSE (D1), and nutraceuticalSFE (D2). The five studies included in the experiment were control, ulcerogenic, inflammatory, hepatotoxicity, and nephrotoxicity. NutraceuticalSFE showed highest decline in gastric juice volume, gastric juice acidity and ulcer index (63.54, 47.33, and 51.65%, respectively) followed by nutraceuticalCSE (41.09, 27.63, and 38.71%, respectively) in ulcerogenic study. Likewise, the maximum decline in paw edema was observed in inflammatory study, as 30.43% and 24.54%, in D2 and D1, respectively. For study IV, the maximum decline in ALT, ALP, AST and bilirubin value was recorded during hepatotoxic study among all other studies i.e. 10.90 & 18.49%, 11.94 & 20.37%, 9.49 & 13.49% and 12.39 & 16.57% for D1 and D2, respectively. A maximum reduction in urea, uric acid and creatinine was found in study V i.e. 20.57 & 28.40%, 20.74 & 33.60% and 14.18 & 23.88%, in D1 and D2 groups, respectively, among all studies. From the findings of the current study, it can by concluded that fennel-based extracts (nutraceuticalCSE and nutraceuticalSFE) are effectual to alleviate from the burden of lifestyle related disorders.
Keywords: Efficacy; In Vivo; Antiulcer; Inflammatory; Hepatotoxic; Nephrotoxic